LIFE AND ITS VALUE IN ISLAM - Hedayetullah, Muhammad (Journal of Dharma, 1996)
To write on a subject like the present one, one should begin with the teaching of the Qur’än -the sacred sciipture of Islam - in order to examine the kind of life and its value prescribed therein. A careful study of the message of the Qur’ãnic teaching makes it clear "that the basic élan of the Qur’an is moral, whence flows its emphasis on monotheism as well as on social justice"l . Moral law is God’s "Command", man must submit to it, this submission is catted Isläm, 2 and its implementation is called "Service" (lbãdat p to God. Because the Qur’änic emphasis is on the moral law, the One God (Allãh) that it commands is primarily the God of justice, mercy, compassion, forgiveness, etc., and the belief that it prescribes is called ’ethical monotheism’.